Electrodeposition Of (Pyrrole-Co-Phenol) On Steel Surfaces In Mixed Electrolytes Of Oxalic Acid And DBSA - Mahmoudian, M.R.; Basirun, Wan Jefrey; Alias, Y. (Elsevier, 2010)
Poly (pyrrole-co-phenol) (co-PyPh) was synthesised using cyclic voltammetry in the mixture of dodecyl benzene sulphonic acid (DBSA) with oxalic acid solution on steel electrodes The morphology and compositions were characterized by Field Emission Scanning Electron Microscopy (FESEM) Fourier Transform Infrared Spectroscopy (FTIR) techniques and Energy-dispersive X-ray spectroscopy (EDX) Electrode/co-PyPh/electrolyte system was studied in 0 1 M NaCl solutions by Electrochemical Impedance Spectroscopy (EIS) The Warburg impedance observed in mid frequency region is an evidence of the effective barrier behaviour of coating The results of EDX indicate that the content of doped sulphur can influence the morphology of co-PyPh Three dissimilar morphologies of co-PyPh and different amount of doped sulphur in co-PyPh are observed The existence of phenol monomer leads to a decrease in the amount of doped sulphur in co-PyPh compared with synthesised polypyrrole (PPy) in the same environment (c) 2010 Elsevier B V All rights reserved